Surface-modified inorganic oxide powder and its manufacturing method

By surface modification of the inorganic oxide powder, powder with specific structure and characteristics is formed, which solves the problem of insufficient charge characteristics and spacing effect in the ink mixing agent by the silicone method, and improves the fluidity and durability of the ink mixing agent.

JP7624286B2Active Publication Date: 2025-01-30NIPPON AEROSIL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021036550
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-08
Publication Date
2025-01-30
Estimated Expiration
2041-03-08

AI Technical Summary

Technical Problem

In the prior art, when the silicone powder prepared by the silicone method is used as an admixture of the ink adjusting agent, there are problems such as weak charge characteristics, easy to absorb moisture, easy to detach from the surface of the ink adjusting agent, and does not have sufficient spacing effect, resulting in a decrease in fluidity and insufficient durability during long-term use of the ink adjusting agent.

Method used

The surface-modified inorganic oxide powder designed with specific structures and characteristics is formed by mixing the inorganic oxide particles with the organosilane compound and heat treatment at 120-360°C to form a moderate charge characteristic of 0.1-1 μm average particle size, a high density of 20-100 g/L, a hydrophobicity of more than 60%, a low water absorption of 2-5%, a high specific surface area of ​​25-150 m²/g and a moderate charge characteristic of -100~-500 μC/g.

Benefits of technology

It achieves the good spacing effect and moderate charge characteristics in the ink adjuster, improves the fluidity and durability of the ink adjuster, and reduces the wear and image defects of the ink adjuster in the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007624286000003
    Figure 0007624286000003
  • Figure 0007624286000004
    Figure 0007624286000004
  • Figure 0007624286000005
    Figure 0007624286000005
Patent Text Reader

Abstract

To provide powder having both a satisfactory spacer effect and suitable charging properties while maintaining excellent characteristics of inorganic oxide powder by a fumed method.SOLUTION: Surface modified inorganic oxide powder showing negative chargeability consists of inorganic oxide particles and particles comprising an organic silicon compound covering the surfaces of the particles and satisfies the following physical properties: (1) the average particle diameter is 0.1 to 1 μm, (2) bulk density is 20 to 100 g / L, (3) hydrophobicity is 60% or more, (4) moisture adsorption under the water vapor relative pressure of 0.8 to 0.95 is 2 to 5%, (5) BET specific surface area is 25 to 150 m2 / g, (6) the content of carbon is 0.5 to 8 wt.% and (7) frictional electrification quantity is -100 to -500 μC / g.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a novel surface-modified inorganic oxide powder and a method for producing the same. [Background technology]

[0002] By treating the surface of fine inorganic oxide powder such as silica, titania, alumina, etc. with an organic substance, it is possible to modify the chargeability, hydrophobicity, etc. of the powder surface. The surface-modified inorganic oxide powder thus obtained is widely used as a flowability improver, chargeability regulator, etc. for toners used in electrophotography including copying machines, laser printers, plain paper facsimiles, etc. Such surface-modified inorganic oxide powders used for toner applications are known as so-called external additives.

[0003] Surface treatment agents for inorganic oxide powders used in toner applications include, for example, organosilicon compounds such as dimethyldichlorosilane, hexamethyldisilazane, and silicone oil. By surface treatment with these organosilicon compounds, for example, silanol groups on the surface of silica fine particles can be replaced with organic groups to perform hydrophobic treatment. As such surface-treated inorganic oxide powders, fumed oxides are widely used as materials that impart high fluidity to toner materials.

[0004] The toner is stirred in a device such as a copier, and is charged (i.e., is charged) by friction with the carrier, etc. Then, the toner can exhibit a developing function due to the highly controlled chargeability. However, if the toner is continuously stirred in the device for a long time, the strong frictional force becomes stress, and the toner deteriorates. For example, if an external additive is embedded in the toner surface, it loses its function as a contact point between the toner surface and the external environment. Moreover, the mechanical load on the toner has increased in recent years, and the hardness of the toner matrix has decreased due to the softening design of the binding resin (toner matrix resin) that constitutes the toner, so that the external additive is more likely to be embedded. For this reason, the importance of measures against the embedding of the external additive as described above is increasing.

[0005] In particular, in recent years, the improvement in image quality of electrophotography has led to the advancement of smaller toner particles, and in addition, the mechanical load on the toner has increased due to the increased speed and colorization. Therefore, the durability of toner performance over time (control of deterioration behavior) is becoming increasingly important, but at the same time, low-temperature fixability is required for the binding resin used in toner in order to reduce printing standby time and save energy. For these reasons, it is becoming mainstream to use components with softer and lower melting points as the toner base resin.

[0006] As the melting point of toner resins is lowered, the surface-treated fumed oxides become embedded in the toner resin during long-term operation, causing a decrease in the fluidity of the toner resin. Therefore, in order to improve the durability of the toner, a submicron-sized silica powder is added to the toner surface together with the fumed oxides, and the submicron-sized silica powder exerts a spacer effect to prevent the fumed oxides from being embedded in the toner. As the submicron-sized silica, silica powder produced by the sol-gel method is mainly used (see Patent Document 1, etc.).

[0007] However, silica powder produced by the sol-gel method has a problem in that it has poor charging properties, which is believed to be due in part to the high amount of moisture adsorbed by the particles that make up the silica powder produced by the sol-gel method.

[0008] Moreover, the silica powder produced by the sol-gel method has a nearly spherical particle shape, and therefore has the problem of being easily separated from the toner surface after long-term use.

[0009] Furthermore, silica powder produced by the sol-gel method is prone to retaining or absorbing a large amount of moisture, and therefore cannot obtain strong triboelectric charging properties. Therefore, in order to adjust the charge, such as in a toner, the low charging property must be improved.

[0010] In contrast, silica powder produced by the dry method or the gas phase method (hereinafter, both are collectively referred to as the "fumed method") has a particle shape that is less spherical than silica produced by the sol-gel method, and is therefore expected to have an effect of suppressing the problem of sol-gel silica being released from the toner surface. However, silica powder produced by the fumed method generally has a small primary particle size and is dispersed on the toner surface as particles of submicron size or less, so it is unable to fully exert the spacer effect, and in addition, its charging characteristics are generally too high, so that in order to control the charging characteristics of the toner within an appropriate range, the amount of addition and dispersibility must be precisely controlled. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] JP 2013-249215 A Summary of the Invention [Problem to be solved by the invention]

[0012] For the reasons mentioned above, there is a strong demand for the development of toner additives (particles) that have appropriate charging properties while being submicron in size so as to fully obtain the spacer effect, but such materials have not yet been developed.

[0013] Therefore, a main object of the present invention is to provide a powder that has both a good spacer effect and appropriate charging characteristics while taking advantage of the excellent properties of inorganic oxide powder produced by the fumed method. [Means for solving the problem]

[0014] As a result of extensive research in light of the problems in the prior art, the inventors have discovered that the above-mentioned object can be achieved by using particles having specific structures and characteristics as external additives, and have thus completed the present invention.

[0015] That is, the present invention relates to the following surface-modified inorganic oxide powder and a method for producing the same. 1. A powder consisting of particles containing inorganic oxide particles and an organosilicon compound that coats the surfaces of the particles, the powder having the following physical properties: (1) Average particle size: 0.1~1μm, (2) Bulk density: 20 to 100 g / L, (3) Hydrophobicity rate: 60% or more, (4) Water adsorption amount at a water vapor relative pressure of 0.8 to 0.95: 2 to 5%; (5) BET specific surface area: 25~150m 2 / g, (6) Carbon content: 0.5 to 8% by weight, and (7) Triboelectric charge: -100 to -500 μC / g A surface-modified inorganic oxide powder exhibiting negative charging properties, characterized in that it has 2. The surface-modified inorganic oxide powder according to item 1, wherein the organosilicon compound is at least one of hexamethyldisilazane, polydimethylsiloxane, and alkylsilane. 3. Inorganic oxide particles have a BET specific surface area of ​​100 to 250 m 2 2. The surface-modified inorganic oxide powder according to claim 1, wherein the surface-modified inorganic oxide powder is fumed silica particles having a particle size of 100 nm / g. 4. An external additive for toner or powder coating, comprising the surface-modified inorganic oxide powder according to any one of items 1 to 3. 5. A toner composition for electrophotography or a powder coating composition comprising the external additive according to item 4 and binder resin particles. 6. A method for producing a surface-modified inorganic oxide powder, comprising: (a) preparing a mixture containing an inorganic oxide powder and an organosilicon compound; (b) heat-treating the mixture at a temperature of 120 to 360°C A method for producing a surface-modified inorganic oxide powder, comprising: 7. The method according to item 6, wherein steps (a) and (b) are carried out under stirring. Effect of the Invention

[0016] According to the present invention, it is possible to provide a powder that has both a good spacer effect and appropriate charging properties while taking advantage of the excellent properties of inorganic oxide powder produced by the fumed method. In particular, inorganic oxide particles produced by a dry method (fumed method or gas phase method) have unique internal pores, and by subjecting the surfaces of such particles to the surface modification specified by the present invention, the bulk density, water adsorption amount, and other properties become specific, so that it is possible to provide a submicron-sized powder that has a low bulk density but appropriate charging properties (negative charging).

[0017] More specifically, the surface-modified inorganic oxide powder of the present invention is prepared by surface-modifying an inorganic oxide powder having internal pores with a specified organosilicon compound, so that each of the properties such as bulk density, hydrophobicity, water adsorption amount, surface area, and carbon content can be controlled within a certain range. As a result, the powder exhibits higher charging characteristics than particles produced by the sol-gel method, and is also capable of achieving sufficient cohesiveness to exhibit a spacer effect that cannot be obtained with silicon oxide powder produced by the conventional fumed method.

[0018] As described above, in order to solve the problems associated with surface-treated sol-gel silica produced by a wet method, the present invention has succeeded in providing a surface-modified inorganic oxide powder that has been surface-treated to improve problems such as decreased toner fluidity that accompanies toners that reduce the environmental impact, and that combines high charging characteristics and low bulk density, which was previously difficult to achieve with sol-gel silica.

[0019] The powder of the present invention having such characteristics can be suitably used as an external additive for toners or powder coatings. Therefore, the toner composition for electrophotography or the powder coating composition containing the surface-modified inorganic oxide powder of the present invention contains the surface-modified inorganic oxide powder having such a high fixation rate and high hydrophobicity, and therefore has excellent flowability, antistatic properties, etc., and suppresses fogging or cleaning failure. Furthermore, it is difficult for the toner to adhere to the photoreceptor, and image defects are unlikely to occur. In addition, the composition of the present invention can also provide effects such as long-term storage stability and control of developer deterioration behavior. [Brief description of the drawings]

[0020] [Figure 1] FIG. 2 is a particle size distribution diagram of the powder obtained in the examples. [Diagram 2] FIG. 2 is a particle size distribution diagram of the powder obtained in the comparative example. [Diagram 3] 1 is a schematic diagram of a method for observing toner particles with an SEM in Test Example 2. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] 1. Surface-modified inorganic oxide powder The surface-modified inorganic oxide powder exhibiting negative chargeability (the powder of the present invention) of the present invention is a powder consisting of particles containing inorganic oxide particles and an organosilicon compound that coats the surfaces of the particles, and has the following physical properties: (1) Average particle size: 0.1~1μm, (2) Bulk density: 20 to 100 g / L, (3) Hydrophobicity rate: 60% or more, (4) Water adsorption amount at a water vapor relative pressure of 0.8 to 0.95: 2 to 5%; (5) BET specific surface area: 25~150m 2 / g, (6) Carbon content: 0.5 to 8% by weight, and (7) Triboelectric charge: -100 to -500 μC / g The present invention is characterized by having the following.

[0022] <Constitution (composition) of the powder of the present invention> The particles constituting the powder of the present invention include inorganic oxide particles and an organosilicon compound that coats the surface of the particles. That is, the basic structure is that an inorganic oxide particle is used as a core particle (base particle), and a part or all of the surface of the core particle is coated with an organosilicon compound.

[0023] The type of inorganic oxide particles to be the core particles is not limited, and examples thereof include, but are not limited to, silicon oxide, titanium oxide, aluminum oxide, etc. Among these, silicon oxide (silica) can be preferably used in the present invention. These particles themselves can be publicly known or commercially available.

[0024] The particle size of the inorganic oxide particles is not limited, but usually, the primary particle size is about 5 to 150 nm. The BET specific surface area of ​​the inorganic oxide is usually 30 to 400 m 2 / g, but is not limited thereto.

[0025] In addition, the method for producing inorganic oxide particles preferably uses powder produced by the fumed method. The fumed method is a known method, and for example, silica can be synthesized by a method including a step of introducing a silicon compound (such as silicon tetrachloride) or metallic silicon into an oxygen-hydrogen flame to cause a hydrolysis reaction. As described above, such powder has a particle shape that is less spherical than silica produced by the sol-gel method, and therefore has the advantage of being able to effectively suppress separation from the toner surface. In addition, since no solvent is used, there is also the advantage that no aggregated particles are generated during drying.

[0026] The inorganic oxide particles produced by the fumed method may be publicly known or commercially available. For example, the commercially available products shown in the examples below may be suitably used.

[0027] The organosilicon compound for coating the surface of the inorganic oxide particles is not particularly limited, and for example, known or commercially available compounds known as hydrophobic treatment agents can be used.

[0028] More specifically, usable compounds include alkylsilazane compounds such as hexamethyldisilazane, alkylalkoxysilane compounds such as dimethyldimethoxysilane, diethyldiethoxysilane, trimethylmethoxysilane, methyltrimethoxysilane, and butyltrimethoxysilane, and chlorosilane compounds such as dimethyldichlorosilane and trimethylchlorosilane, as well as silicone oils such as polydimethylsiloxane (PDMS), silicone varnishes, etc. These compounds may be used alone or in combination of two or more.

[0029] Among these, in order to more reliably obtain the effects of the present invention, it is preferable to use at least one of an alkylsilazane compound, an alkylalkoxysilane compound, and a silicone oil, and more preferably at least one of hexamethyldisilazane, polydimethylsiloxane, and an alkylalkoxysilane.

[0030] In particular, the alkylalkoxysilane compound is not particularly limited as long as it is an alkoxysilane having an alkyl group, and examples thereof include trimethoxyalkoxysilane and triethoxyalkoxysilane. The number of carbon atoms (C) of the alkyl group is not particularly limited, but is preferably C2 to C18. If it is less than C2, there is a risk of volatilization of the alkoxysilane during the surface treatment. If it exceeds C16, strong aggregation may occur due to the influence of the high viscosity, and the dispersibility of the obtained powder may be impaired.

[0031] In particular, as the silicone oil, in addition to polydimethylsiloxane, modified silicone oils into which, for example, alkyl groups, -OH groups, etc. have been introduced can also be used.

[0032] The viscosity range of the organosilicon compound (measurement temperature 25°C) is not particularly limited, but is usually preferably 20 to 300cs. If the viscosity is less than 20cs, low molecular weight polysiloxanes and the like will volatilize during surface treatment, which is undesirable from the viewpoints of energy efficiency and the environment. On the other hand, if the viscosity exceeds 300cs, higher aggregation will occur, and the dispersibility of the obtained powder may be impaired.

[0033] The content of the organosilicon compound in the powder of the present invention is not particularly limited as long as it is within the above-mentioned carbon content range, but it is generally about 5 to 20 parts by weight, and preferably 10 to 15 parts by weight, per 100 parts by weight of the inorganic oxide powder.

[0034] <Characteristics of the powder of the present invention> The powder of the present invention has the following characteristics: (1) Average particle size: 0.1~1μm, (2) Bulk density: 20 to 100 g / L, (3) Hydrophobicity rate: 60% or more, (4) Water adsorption amount at a water vapor relative pressure of 0.8 to 0.95: 2 to 5%; (5) BET specific surface area: 25~150m 2 / g, (6) Carbon content: 0.5 to 8% by weight, and (7) Triboelectric charge: -100 to -500 μC / g Satisfy all of the following.

[0035] Average particle size The average particle size is usually about 0.1 to 1 μm, and preferably 0.2 to 0.8 μm. By having a particle size within the above range, the function as a spacer can also be effectively fulfilled. The average particle size in the present invention refers to a value (arithmetic mean diameter (volume standard)) calculated using a particle size distribution measuring device (laser diffraction scattering type particle size distribution measuring device (manufactured by Horiba, Ltd.)).

[0036] Bulk density The bulk density is usually about 20 to 100 g / L, and preferably 30 to 80 g / L. If the bulk density is less than 20 g / L, the powder cannot be dispersed with an appropriate aggregate particle size when dispersed on the toner surface, and a sufficient spacer effect cannot be exhibited. If the bulk density exceeds 100 g / L, a large device volume is required when mixing with the toner, which is problematic for industrial use.

[0037] Hydrophobicity The hydrophobicity is usually about 60% or more, preferably 97% or more, and more preferably 99% or more. The hydrophobicity in the present invention is an index showing the degree of hydrophobicity of the surface-modified inorganic oxide powder. If the hydrophobicity is less than 60%, the inorganic oxide powder may not be able to retain strong electrostatic properties due to the residual silanol groups, and a submicron-sized powder with excellent electrostatic properties may not be obtained. The upper limit of the hydrophobicity is not particularly limited, but is usually 100%.

[0038] Moisture adsorption amount The moisture adsorption amount at a water vapor relative pressure of 0.8 to 0.95 is usually about 2 to 5% by weight, and preferably 2.5 to 4.0% by weight. The moisture adsorption amount has a large effect on the charging characteristics, and by setting it within the above range, it is possible to impart an appropriate charging property. If the moisture adsorption amount is less than 2% by weight, for example, silica powder will exhibit the charging characteristics specific to fumed silica, and will become too strongly negatively charged. If the moisture adsorption amount exceeds 5% by weight, the retained and adsorbed moisture amount will be close to that of silica produced by the sol-gel method, and sufficient charging characteristics will not be exhibited.

[0039] BET specific surface area The BET specific surface area is usually 25 to 150 m 2 / g, especially 30~130m 2 / g. The BET specific surface area is preferably 25 m 2 If the BET specific surface area is less than 150 m / g, the aggregate particle size will be too large and the dispersibility will be insufficient when dispersed in a toner. 2If it exceeds 1 / g, the appropriate aggregation diameter is not maintained when dispersed in the toner, and a sufficient spacer effect cannot be exhibited.

[0040] Carbon Content The carbon content is usually about 0.5 to 8% by weight, preferably 0.8 to 6.0% by weight. In particular, when the surface treatment agent (hydrophobic treatment agent) is HMDS, it is preferably about 0.5 to 2.0% by weight, when it is PDMS, it is preferably about 0.5 to 8.0% by weight, and when it is alkylalkoxysilane, it is preferably about 0.5 to 8.0% by weight. The carbon content is an index showing the degree of fixation (fixed amount) to the inorganic oxide powder by the organic silicon compound which is the surface treatment agent. If the carbon content is too low, the surface is not sufficiently modified, the hydrophobicity cannot be sufficiently given, and the charging characteristics, dispersibility, etc. become insufficient. On the other hand, if the carbon content is too high, the organic matter content is too high, so that the particles aggregate, and sufficient fluidity and dispersibility cannot be obtained, and even if this powder is applied to a toner, a sufficient spacer effect cannot be expressed.

[0041] Triboelectric charge The triboelectric charge is usually about -100 to -500 μC / g, and preferably -150 to -350 μC / g. If the triboelectric charge approaches zero from -100 μC / g, it becomes difficult to impart strong charging characteristics to the toner when the powder is added to the toner, and it becomes difficult to control the toner within a predetermined charge range. On the other hand, if the triboelectric charge becomes more negative than -500 μC / g, it becomes difficult to control the charging characteristics of the toner to which it is added due to the strong triboelectric charge.

[0042] 2. Method for producing the powder of the present invention The method for producing the powder of the present invention is not particularly limited as long as it can produce a powder having the above-mentioned composition and characteristics. For example, the powder of the present invention can be suitably produced by a method including: (a) a step of preparing a mixture containing an inorganic oxide powder and an organosilicon compound (mixture preparation step); and (b) a step of heat-treating the mixture at a temperature of 120 to 360°C (heat treatment step).

[0043] Mixture preparation process The mixture preparation step can be carried out by any method that can coat the surface of each particle constituting the inorganic oxide powder with an organosilicon compound. For example, a method of mixing an inorganic oxide powder with a vaporized organosilicon compound under stirring, or a method of spraying an organosilicon compound onto an inorganic oxide powder under stirring can be suitably employed.

[0044] In this case, the organosilicon compound may be used in a state of being dissolved or dispersed in a solvent (e.g., an organic solvent such as hexane or toluene) as necessary. In this case, the concentration of the organosilicon compound may be appropriately set depending on the type of organosilicon compound used, etc.

[0045] In the present invention, water and a catalyst (such as an amine) can also be appropriately added to the mixture, if necessary.

[0046] The temperature conditions in the mixture preparation step are not particularly limited, and may be, for example, within the range of 10 to 40° C., but are not limited thereto. In addition, the atmosphere is usually preferably an inert gas atmosphere. For example, nitrogen gas, helium gas, argon gas, etc. can be suitably used.

[0047] The type, amount, etc. of the organosilicon compound may be the same as those explained in "1. Surface-modified inorganic oxide powder" above.

[0048] Heat Treatment Process The heat treatment temperature in the heat treatment step is not limited, but is usually preferably 120 to 360°C (particularly 150 to 300°C). If the heat treatment temperature exceeds 360°C, the organosilicon compound may partially decompose. If the heat treatment temperature is less than 120°C, the surface of the organosilicon compound may not be sufficiently modified, and the desired hydrophobicity may not be obtained.

[0049] The heat treatment is preferably performed in an inert gas atmosphere, as in the above-mentioned process. For example, nitrogen gas, helium gas, argon gas, etc. can be suitably used. In particular, the above-mentioned process is performed in a sealed reactor, and the heat treatment process can be suitably performed while maintaining the atmosphere.

[0050] The heat treatment time may be a time sufficient for the organosilane compound to be fixed (adhered) to the surface of each particle constituting the inorganic oxide powder, and may be, for example, about 10 to 200 minutes, but is not limited to this.

[0051] 3. Use of the powder of the present invention The powder of the present invention has all of the properties (1) to (7) shown in "1. Surface-modified inorganic oxide powder" above, and therefore exhibits both a good spacer effect and appropriate charging properties in addition to the excellent properties of inorganic oxide powder produced by the fumed method. Therefore, the powder of the present invention can be suitably used as an additive (particularly an external additive for toner) for toners, powder coatings, etc. Accordingly, the present invention also includes an electrophotographic toner composition or powder coating composition containing the powder of the present invention and binding resin particles (hereinafter, both are also collectively referred to as "the composition of the present invention").

[0052] The composition of the present invention contains the above-mentioned surface-modified inorganic oxide powder of the present invention, and there are no particular limitations on its composition, production method, etc., and any known composition and method may be used.

[0053] The content of the powder of the present invention in the composition of the present invention is not particularly limited as long as the desired property improvement effect is obtained, but it is usually preferable that the content is about 0.1 to 5.0% by weight. If the content of the surface-modified inorganic oxide powder of the present invention in the composition of the present invention is less than 0.1% by weight, the effect of improving the flowability or the effect of stabilizing the chargeability due to the addition of the surface-modified inorganic oxide powder may not be sufficiently obtained. In addition, if the content of the surface-modified inorganic oxide powder exceeds 5.0% by weight, the surface-modified inorganic oxide powder may act independently, and problems may occur, for example, in images, cleaning properties, etc.

[0054] In addition to the binder resin particles, the composition of the present invention may contain, as necessary, for example, a pigment, a charge control agent (charge control agent), wax, etc. These components may be the same as those in known or commercially available toner compositions. In addition, the type of toner is preferably a negatively charged toner, but is not particularly limited in other respects. Therefore, for example, either a magnetic or non-magnetic one-component toner or a two-component toner may be used. Furthermore, either a monochrome or color toner may be used.

[0055] The powder of the present invention has particularly excellent spacer effect and can therefore be suitably used as an external additive for adhesive resin particles containing a resin component that is easily softened (e.g., at least one of styrene-acrylic copolymer resin, polyester resin, epoxy resin, etc.).

[0056] In the toner composition for electrophotography of the present invention, the powder of the present invention as an external additive is not limited to being used alone, but may be used in combination with other metal oxide fine powders depending on the purpose. For example, the surface-modified inorganic oxide powder of the present invention may be used in combination with other surface-modified dry silica fine powders, surface-modified dry titanium oxide fine powders, surface-modified wet titanium oxide fine powders, etc., as necessary. EXAMPLES

[0057] The features of the present invention will be described in more detail below with reference to examples and comparative examples, although the scope of the present invention is not limited to the examples.

[0058] The components used in each of the examples and comparative examples are as follows. (A) Silica powder (A1) Sol-gel silica The sample was prepared by a known sol-gel method (BET specific surface area 30 m 2 / g) (A2) Sample A A sample with internal voids produced by a known fumed method (BET specific surface area 110 m 2 / g) (A3) Sample B A sample with internal voids produced by a known fumed method (BET specific surface area 120 m 2 / g) (A4) Commercially available product a Product name: "AEROSIL TT600" (registered trademark) manufactured by Nippon Aerosil Co., Ltd. (fumed silica, BET specific surface area 135 m 2 / g) (A5) Sample C A sample with internal voids produced by a known fumed method (BET specific surface area 165 m 2 / g) (A6) Sample D A sample with internal voids produced by a known fumed method (BET specific surface area 210 m 2 / g) (A7) Commercially available product b Product name: "AEROSIL OX50" (registered trademark) manufactured by Nippon Aerosil Co., Ltd. (fumed silica, BET specific surface area 50 m 2 / g) (A8) Commercially available products Product name: "AEROSIL 90G" (registered trademark) manufactured by Nippon Aerosil Co., Ltd. (fumed silica, BET specific surface area 90 m 2 / g) (B) Surface treatment agents (B1) HMDS Hexamethyldisilazane (product name: "Dynasilane HMDS" (registered trademark) manufactured by Evonik) (B2) PDMS (A) Polydimethylsiloxane (product name "KF96-20cs" manufactured by Shin-Etsu Chemical Co., Ltd.) (B3) PDMS (B) Polydimethylsiloxane (product name "KF96-300cs" manufactured by Shin-Etsu Chemical Co., Ltd.) (B4) Alkylsilane A Alkylsilane-based surface treatment agent (product name: DOWSIL Z-6329 (registered trademark), manufactured by Dow and TOYAY) (B5) Alkylsilane B Alkylsilane surface treatment agent (product name "Dynasilan 9116" (registered trademark) manufactured by Evonik)

[0059] [Example 1] Sample A (100 parts by weight) was placed in a reactor as silica powder, and alkylsilane B (10 parts by weight) was added as a surface treatment agent while stirring in a nitrogen atmosphere. The mixture was then heat-treated at 150°C for 60 minutes with continued stirring to obtain a surface-modified silica powder having internal pores.

[0060] [Example 2] A surface-modified silica powder was obtained in the same manner as in Example 1, except that the silica powder was changed to Sample B (100 parts by weight) and the surface treatment agent was changed to PDMS (B) (15 parts by weight).

[0061] [Example 3] A surface-modified silica powder having internal pores was obtained in the same manner as in Example 1, except that the silica powder was changed to commercially available product A4 and the surface treatment agent was changed to HMDS.

[0062] [Example 4] A surface-modified silica powder having internal pores was obtained in the same manner as in Example 1, except that the doped silica powder was changed to commercially available product A4 and the surface treatment agent was changed to PDMS (A).

[0063] [Example 5] The surface treatment of the dry silica having internal voids was carried out in the same manner as in Example 4, except that the amount of PDMS (A) added was changed to 15 parts by weight.

[0064] [Example 6] A surface-modified silica powder having internal pores was obtained in the same manner as in Example 1, except that sample C (100 parts by weight) was used as the silica powder and PDMS (A) (15 parts by weight) was used as the surface treatment agent.

[0065] [Example 7] A surface-modified silica powder having internal pores was obtained in the same manner as in Example 1, except that sample C (100 parts by weight) was used as the silica powder and alkylsilane (A) was used as the surface treatment agent.

[0066] [Example 8] A surface-modified silica powder having internal pores was obtained in the same manner as in Example 1, except that sample D (100 parts by weight) was used as the silica powder and alkylsilane (A) (15 parts by weight) was used.

[0067] [Example 9] A surface-modified silica powder having internal pores was obtained in the same manner as in Example 1, except that sample D (100 parts by weight) was used as the silica powder and the surface treatment agent was changed to 5 parts by weight of HDMS and 5 parts by weight of PDMS (A) (total 10 parts by weight).

[0068] [Example 10] A surface-modified silica powder having internal pores was obtained in the same manner as in Example 1, except that sample A (100 parts by weight) was used as the silica powder and the surface treatment agent was changed to 5 parts by weight of alkylsilane B and 5 parts by weight of PDMS (B) (total 10 parts by weight).

[0069] [Comparative Examples 1 to 3] Sol-gel silica (100 parts by weight) was placed in a reactor as silica powder, and while stirring in a nitrogen atmosphere, the surface treatment agent shown in Table 2 was added in the specified amount, and the mixture was heat-treated while continuing to stir, thereby obtaining a surface-modified silica powder.

[0070] [Comparative Examples 4 to 6] Commercially available silica powder b (100 parts by weight) was placed in a reactor, and the surface treatment agent shown in Table 2 was added in a prescribed amount while stirring in a nitrogen atmosphere. The mixture was then heat-treated while continuing to stir, to obtain a surface-modified silica powder.

[0071] [Comparative Examples 7 to 9] Commercially available silica powder c (100 parts by weight) was placed in a reactor, and the surface treatment agent shown in Table 2 was added in a prescribed amount while stirring in a nitrogen atmosphere. The mixture was then heat-treated while continuing to stir, to obtain a surface-modified silica powder.

[0072] [Test Example 1] The surface-modified silica powders obtained in the respective Examples and Comparative Examples were measured for the following physical properties. The results are shown in Tables 1 and 2.

[0073] (1) Bulk density Place the measuring cylinder on a top-loading balance, erase the tare, pour the sample into the measuring cylinder and measure its mass (mass A), then read the volume after leaving it to stand for 2 minutes (volume B). Calculate the bulk density using the following formula: Bulk density (g / L) = (mass A / volume B) x 1000

[0074] (2) Hydrophobicity 1 g of surface-modified silica powder was weighed and placed in a 200 mL separatory funnel, 100 mL of pure water was added, the funnel was plugged, and the funnel was shaken at 90 rpm for 10 minutes with a Turbula mixer. After shaking, the funnel was left to stand for another 10 minutes, and then 20 to 30 mL of the lower layer was removed from the funnel. The lower layer mixture was then separated into a 10 mm quartz cell, and the colorimeter was used with pure water as a blank, and the light transmittance (%) at a wavelength of 500 nm was taken as the hydrophobicity. The higher the light transmittance, the higher the hydrophobicity. This is because highly hydrophobic surface-modified inorganic oxide powders tend to float on the water surface without dispersing in the water, which makes the water less likely to become cloudy and increases the light transmittance.

[0075] (3) Moisture adsorption measurement The surface-modified silica powder is heated under vacuum at 150°C for more than 2 hours and thoroughly dried, and then measured using a high-precision gas adsorption measurement device (product name "BELSORP-max" manufactured by Microtrack Bell Co., Ltd.) under conditions of an evacuation time of 15 minutes and a pressure rise allowance of 5.000E-1 Pa / min. The adsorption isotherm is analyzed, and the value within the range of water vapor relative pressure of 0.8 to 0.95 is taken as the water adsorption amount.

[0076] (4) BET specific surface area BET{Surface area(m 2 The specific surface area (g) was calculated using a fully automatic specific surface area measuring device (product name "Macsorb", Mountec) by pretreating the sample at 100°C for 10 minutes, and then calculating the surface area of ​​the sample from the amount of nitrogen adsorbed and desorbed by the BET single-point method, and dividing the surface area by the weight to obtain the specific surface area.

[0077] (5) Carbon content The carbon content was measured using a carbon analyzer (product name "SUMIGRAPH NC-22" manufactured by Sumika Chemical Analysis Center). (6) Amount of triboelectric charge

[0078] 2 g of the surface-modified silica powder and 48 g of the iron powder carrier were placed in a glass container (volume 75 mL) and shaken for 10 minutes with a Turbula mixer. 0.05 g of the mixture was then sampled and the amount of triboelectric charge was measured using a suction blow-off type Q / M meter (product name "MODEL 230TO" Trek Japan Co., Ltd.).

[0079] (7) Particle size distribution measurement Measurements were performed using a laser diffraction particle size distribution analyzer (product name "LA-920" manufactured by Horiba, Ltd.). Ethanol was used as the dispersion medium, and after adding the sample, measurements were performed under dispersion conditions of circulation intensity: 10, ultrasonic intensity: 7, ultrasonic irradiation time: 3 minutes, and the range of particle size distribution within the arithmetic mean diameter was taken as the aggregate particle diameter.

[0080] [Test Example 2] The surface-modified silica powder obtained in each of the Examples and Comparative Examples was mixed with a commercially available negatively charged polyester toner base (binding resin) powder produced by a polymerization method in a weight ratio of 99:1, and premixed in a Henschel mixer at 600 rpm for 1 minute, and then mixed at 3,000 rpm for 30 minutes to prepare a toner sample for dispersibility evaluation. Next, the obtained toner sample was observed with a scanning electron microscope (SEM) to determine whether the surface of the toner sample particle was within 1 μm 2 The number of surface-modified silica particles with a particle size of 0.1 μm or more adhering per unit area was counted. The results are also shown in Table 1. The measurement was carried out by arbitrarily selecting one toner base (toner particle) within the field of view of the SEM, and setting the field of view S as shown in FIG. 3 so that the field of view S was filled with the surfaces of the toner particles 10 and contained as many surface-modified silica particles 11 as possible. After counting the number of all surface-modified silica particles 11 within the field of view S, the number was divided by the area of ​​the field of view to obtain the number of surface-modified silica particles per unit area (1 μm 2The number of surface-modified silica particles (per unit) was calculated. In this case, any surface-modified silica particles protruding even slightly from the field of view S were not counted.

[0081] [Test Example 3] The particle size distribution of each of the powders obtained in Examples 3, 6 and 8 and Comparative Examples 3 and 8 was examined. The particle size distribution was measured in the same manner as described above in "(7) Measurement of particle size distribution." The results are shown in Figures 1 and 2.

[0082] [Table 1]

[0083] [Table 2]

[0084] As is clear from the results in Tables 1 and 2 and Figures 1 and 2, the powders of the examples satisfy all of the characteristics stipulated in the present invention. In particular, they are submicron-sized powders with appropriate charging characteristics (negative charging characteristic of -150 to -482 μC / g) despite their low bulk density of 35 to 82 g / L.

Claims

1. A powder comprising particles containing silicon oxide particles as inorganic oxide particles and an organosilicon compound coating the surfaces of the particles, the powder having the following physical properties: (1) Average particle size: 0.1 to 1 μm, (2) Bulk density: 20 to 82 g / L, (3) Hydrophobicity: 60% or more, (4) Water adsorption amount at a water vapor relative pressure of 0.8 to 0.95: 2 to 5%; (5) BET specific surface area: 25-150 m 2 / g, (6) Carbon content: 0.5 to 8% by weight, and (7) Triboelectric charge: -100 to -500 μC / g A surface-modified inorganic oxide powder exhibiting negative charging properties, characterized in that it has

2. 2. The surface-modified inorganic oxide powder of claim 1, wherein the organosilicon compound is at least one of hexamethyldisilazane, polydimethylsiloxane, and alkylalkoxysilane.

3. The inorganic oxide particles have a BET specific surface area of ​​100 to 250 m 2 2. The surface-modified inorganic oxide powder of claim 1, wherein the powder is fumed silica particles having a particle size of about 1 / g.

4. An external additive for toner or powder coating, comprising the surface-modified inorganic oxide powder according to any one of claims 1 to 3.

5. 5. A toner composition or a powder coating composition for electrophotography, comprising the external additive according to claim 4 and binder resin particles.

Citation Information

Patent Citations

  • Agent for improving fluidity of negatively charging resin powder

    JP1989203478A

  • External additive for toner

    JP2004144854A

  • Hydrophobic spherical silica minute particle, its manufacturing method, and toner additive therewith for electrostatic charge image development

    JP2005015251A

  • Surface treatment method of hydrophilic sol-gel silica particle

    JP2013249215A

  • Superfine silica powder and application thereof

    JP2016138011A